2020
DOI: 10.1177/1464420720930754
|View full text |Cite
|
Sign up to set email alerts
|

Multi-pass laser cutting of carbon/Kevlar hybrid composite: Prediction of thermal stress, heat-affected zone, and kerf width by thermo-mechanical modeling

Abstract: Numerical modeling offers considerable promise to reduce costs associated with trial-and-error process in the manufacturing industry. In laser cutting of fiber-reinforced composites, the developed thermal stress in the cut region has considerable influence on the application of the machined composite and the end product quality. Nevertheless, measurement of the thermal stress is quite challenging in practice. Here, an uncoupled thermo-mechanical finite element model is developed to accurately predict formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Moghadasi et al developed an uncoupled thermomechanical FE model to simulate LBM on a carbon/Kevlar hybrid composite, as shown in figure 4 [61]. The numerical results for the HAZ and kerf width with respect to the fiber orientation and thermal conductivity agreed well with the experimental results, although a discontinuity existed in the temperature owing to the different thermal conductivities of the fibers.…”
Section: Numerical Simulationmentioning
confidence: 74%
“…Moghadasi et al developed an uncoupled thermomechanical FE model to simulate LBM on a carbon/Kevlar hybrid composite, as shown in figure 4 [61]. The numerical results for the HAZ and kerf width with respect to the fiber orientation and thermal conductivity agreed well with the experimental results, although a discontinuity existed in the temperature owing to the different thermal conductivities of the fibers.…”
Section: Numerical Simulationmentioning
confidence: 74%
“…It is interesting to note that although SOD at a lower position produces an extensive affected area, it cannot produce a suitable result. This can be attributed to the nature of the Gaussian beam in which the power density is not evenly distributed across the beam spot [ 14 , 15 ]. Table 2 shows samples at SODs of 47.8 and 48.8 mm, both of which result in a burnt area at the top surface of the paints.…”
Section: Resultsmentioning
confidence: 99%
“…The material removal was achieved using the element-death method, a simplified approach where elements are deactivated from the model once they reach a certain critical temperature threshold. Previous investigations [ 10 , 11 , 12 , 14 , 15 ] demonstrated that this technique is suitable for simulating the material removal process during laser cutting. When the focus was set to a larger scale, it was acceptable that phenomena such as the phase transition, vaporization effects, and vapour or melt dynamics, which occur during the laser material interaction, were neglected.…”
Section: Methodsmentioning
confidence: 99%
“…This kind of model enables the representation of direction-dependent material behaviour in a higher order of magnitude, although the detailed distinction between the fibre and matrix is omitted. For instance, Long [ 14 ] conducted a study simulating the laser ablation of CFRP using a continuous wave (CW) laser, while Moghadasi [ 15 ] employed a combination of both approaches to investigate a Kevlar/CFRP composite. While the properties of CFRP are homogenised, a weave of both materials is modelled as heterogeneous.…”
Section: Introductionmentioning
confidence: 99%